FORMULASI DAN EVALUASI SEDIAAN SIRUP DAUN SEREH (Cymbopogon citratus) - dina febrina (Universitas Harapan Bangsa Purwokerto, 2018)
ABSTRACT Lemongrass (Cymbopogon citratus) is one of the plants commonly used as spices by the people of Indonesia. However, the use of lemongrass as cooking spices is only located on the stem, while the lemongrass leaves are still a waste. Even though lemongrass leaves are known to contain phenol active compounds which can act as antioxidants. Lemongrass syrup formulations are made into 3 formulas, Formula I 0,75: 0,25; Formula II 0,25: 0,75; Formula III 0,5: 0,5 for sucrose: Na CMC. Formulation I with sucrose levels: Na CMC (0,75: 0,25) has the most desirable taste and for evaluation has the best value.